Large pore dermal microdialysis and liquid chromatography‐tandem mass spectroscopy shotgun proteomic analysis: a feasibility study. Issue 4 (28th March 2013) - Petersen, Lars J.; Sørensen, Mette A.; Codrea, Marius C.; Zacho, Helle D.; Bendixen, Emøke
<x xml:space="preserve">Abstract</x> Background/Aims The purpose of the present pilot study was to investigate the feasibility of combining large pore dermal microdialysis with shotgun proteomic analysis in human skin. Methods Dialysate was recovered from human skin by 2000 kDa microdialysis membranes from one subject at three different phases of the study; trauma due to implantation of the dialysis device, a post implantation steady‐state period, and after induction of vasodilatation and plasma extravasation. For shotgun proteomics, the proteins were extracted and digested with trypsin. Peptides were separated by capillary and nanoflow HPLC systems, followed by tandem mass spectrometry (MS/MS) on a Quadrupole‐TOF hybrid instrument. The MS/MS spectra were merged and mapped to a human target protein database to achieve peptide identification and protein inference. Results Results showed variation in protein amounts and profiles for each of the different sampling phases. The total protein concentration was 1.7, 0.6, and 1.3 mg/mL during the three phases, respectively. A total of 158 different proteins were identified. Immunoglobulins and the major classes of plasma proteins, including proteases, coagulation factors, apolipoproteins, albumins, and complement factors, make up the major load of proteins in all three test conditions. Conclusion Shotgun proteomics allowed the identification of more than 150 proteins in microdialysis samples from human skin. This highlights the opportunities of LC‐MS/MS to study the complex molecular interactions in the skin.